Magnetik spinel ferit: Doping Ni₁₋ₓMnₓFe₂O₄ sebagai radar absrorbing material - Yolanda Ferliana Putri; Sulthon Nurharmansyah Putra; Gabriel Radika Prabowo (Papanda Journal of Mathematics and Science Research, 2026)
This study investigates the synthesis and characterization of radar absorbing material (RAM) of spinel ferrite based (Ni₁₋ₓMnₓFe₂O) has been performed by hydrothermal method using Mn(NO₃)₂·4H₂O, Fe(NO₃)₃·9H₂O, Ni(NO₃)₂·6H₂O, and CTAB as a precursor. The effect of Mn doping on the structural, optical, and magnetic properties was examined by varying the Mn concentration (x=0-1). X-Ray Diffraction (XRD) analysis confirmed a single-phase cubic spinel structure for all samples, with a shift in diffraction peak observed as the Mn concentration increased, attributable to the difference in ionic radii between Ni2+ and Mn2+. The band gap value decreased with increasing Mn doping, which enhanced electron hopping within the lattice and consequently contributed to the observed dielectric loss. Magnetization tests indicated an increase in magnetization at low doping levels (3 wt%), which strengthened the magnetic loss mechanism, while excessive doping led to a reduction in ferrimagnetic properties, approaching paramagnetic behavior. FESEM revealed agglomerated nanoparticles with sizes ranging form 11–27 nm, this nanoscale dimension is advantageous as it increase the specific surface area for enhanced  interaction with electromagnetic waves. Conclusion, Mn doping successfully enhanced the performance of NiFe₂O₄ system as a candidate for new radar-absorbing materials, with the optimum composition achieved at low doping levels. In practical terms, this material can be applied as a lightweight coating in stealth aircraft technology or as electromagnetic interference (EMI) shielding in modern telecommunications devices.